PENGEMBANGAN BAHAN AJAR BERBASIS AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK BANGUN RUANG KUBUS DAN BALOK KELAS VIII DI SMP N 1 CILEDUG - megan antropa legendari; hendri raharjo (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2016)
As an educator , a teacher must be able to implement and create a conducive learning atmosphere and fun during the learning process takes place so that students can be motivated to learn the spirit . This study aims to : ( 1 ) Develop non-print instructional materials in the form of audio- visual -based teaching materials for students of class VIII SMP Negeri 1 Ciledug , ( 2 ) To determine the students' response to mathematics learning through audio- visual -based teaching materials. The method used in the development of mathematics teaching materials are the kind of research and development ADDIE models . Some stages will be carried out in the research and development are: ( 1 ) analysis , ( 2 ) design , ( 3 ) development , ( 4 ) implementation , and ( 5 ) evaluation . This research resulted in a product such as the development of audio- visual -based teaching materials that have been validated by experts in their field . Furthermore, the results of product testing , to see the effectiveness test which concluded that based on the calculation of Two Independent Sample Test results obtained value Z_hitung > Z_tabel ( -3.917 > -1.96 ) and Asym . Sig ( 2 - tailed ) of 0.000 < 0.05 , thus it can be concluded there is a difference in learning outcomes between the experimental class and the class of the N - gain control , this can be seen in the experimental class rank 50.65 and control class rank of 30 , 35 , thus it can be concluded that the experimental class learning outcomes better than the control class .Keywords: Development of Teaching Materials, Audio-visual.